The attitudes of Iraqi youth towards volunteering work - Abdullah, Nala Najah; ALgubori, Irada Zaydan (ALBAHITH ALALAMI, 2020)
The aim of the research is to identify the attitudes of Iraqi youthtowards volunteering work by using the survey method and the scaletool to identify what young volunteers can carry from the attitudestowards volunteering work because the phenomenon of volunteerwork is of great importance in society. The scale was applied to(525) volunteers among Iraqi youth. The research reached a setof results, the most prominent of which is the existence of positivetrends among young people towards volunteering work, meaningthat Iraqi youth volunteers have awareness of the concept ofvolunteering correctly. As for their goals of volunteering, they arehumanitarian and social goals for the advancement of society, andsocial media was one of the main sources. From social media theIraqi youth volunteers drew their knowledge about volunteeringwork